The cicada genus Selymbria Stå1, 1861 (Hemiptera: Cicadidae: Tibicininae: Selymbrini): redescription including ten new species and a key to the genus - Sanborn, Allen F. (Zootaxa, 2019)
The cicada genus Selymbria Stål, 1861 is redescribed along with ten new species. Selymbria boliviaensis n. sp. is described from Bolivia, S. chevauxensis n. sp. and S. guianensis n. sp. are described from French Guiana, S. cinctifera n. sp. is described from Panama and Costa Rica, S. ecuadorensis n. sp. is described from Ecuador, S. guatemalensis n. sp. is described from Guatemala, S. iguazuensis n. sp. is described from Argentina and Brazil, S. loretoensis n. sp. and S. madredediosensis n. sp. are described from Peru, and S. puntarenasensis n. sp. is described from Costa Rica. The current sixteen species of Selymbria are listed along with their synonymies and the known distribution of each species. A key to the species of Selymbria is provided.